2009
DOI: 10.1068/a41262
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood Reputation and the Intention to Leave the Neighbourhood

Abstract: This is the author's Post-print version (final draft post-refereeing as accepted for publication by the journal). The definitive, peer-reviewed and edited version of this article is published as: Permentier M., van Ham M. and Bolt G. (2009) Neighbourhood reputation and the intention to leave the neighbourhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 59 publications
3
74
1
1
Order By: Relevance
“…Several studies (e.g. Permentier et al, 2009;Tsafti & Cohen, 2003) have shown a relationship between perceived neighbourhood (or town) reputation and intention to move, though this is moderated by place attachment-especially having family living nearby. Indeed, in his study of 12 Danish estates, Skifter-Andersen (2008) reported that the perception of a poor area reputation was the most important influence on plans to move away.…”
Section: Reputation Studies In Recent Neighbourhoods Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (e.g. Permentier et al, 2009;Tsafti & Cohen, 2003) have shown a relationship between perceived neighbourhood (or town) reputation and intention to move, though this is moderated by place attachment-especially having family living nearby. Indeed, in his study of 12 Danish estates, Skifter-Andersen (2008) reported that the perception of a poor area reputation was the most important influence on plans to move away.…”
Section: Reputation Studies In Recent Neighbourhoods Researchmentioning
confidence: 99%
“…Using Hirschman's model for responses to service dissatisfaction, Permentier et al (2007) argue that residential mobility-'the exit option'-is the most 'clear-cut' response to a negative neighbourhood reputation because of the negative effects on a person's status, self-image and well-being (Permentier et al, 2009). Several studies (e.g.…”
Section: Reputation Studies In Recent Neighbourhoods Researchmentioning
confidence: 99%
“…The primary driver of these decisions is household dissatisfaction with the existing dwelling in relation to household preferences and needs (Brown and Moore, 1970;Clark and Dieleman, 1996). The role of neighbourhood characteristics in mobility decisions has received less attention, but the body of literature which includes neighbourhood characteristics in models of residential mobility is growing (Clark and Ledwith, 2006;Feijten and van Ham, 2009;Kearns and Parkes, 2003;Lee et al, 1994;Permentier et al, 2009;van Ham and Clark, 2009;van Ham and Feijten, 2008). Studies investigating the second step in the decision making process (the choice of destination) have mainly focused on dwelling types (tenure, size, price) and less attention has been paid to location and neighbourhood characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is large variation in the types (and quality) of dwellings available between neighbourhoods, making the supply of housing in different neighbourhoods a key explanatory factor behind neighbourhood sorting. However, there are clear indications in the literature that households also take neighbourhood attributes such as reputation, status, population composition, and location into consideration when choosing a dwelling (see for example Michelson, 1977;Permentier et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For other mechanisms such as stigmatisation or the attitudes of 'local market actors' (for instance, employers) to certain neighbourhoods a larger spatial scale is requiredsomething that is akin to a recognisable 'neighbourhood' in the mind of those external to the neighbourhood. In this case neighbourhood reputation (see Permentier et al 2009) and the perceived qualities of the residents could be important with regard to an individual's occupational success.…”
Section: Methodsmentioning
confidence: 99%